2014
DOI: 10.1002/hrm.21629
|View full text |Cite
|
Sign up to set email alerts
|

Work‐To‐Life Conflict and Enrichment Among International Business Travelers: The Role of International Career Orientation

Abstract: The present study examines the direct and moderating effects of an international career orientation in the relationship between frequency and duration of international business traveling and work‐to‐life conflict and enrichment. In addition, the effort‐reward imbalance that potentially features in the international business traveler's job was examined in relation to work‐to‐life conflict and enrichment. The study was conducted among 232 Finnish people in jobs requiring international business travel. A moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 57 publications
4
43
1
2
Order By: Relevance
“…There are at least three earlier studies focussing on work-family or work-life interaction among IBTs ( Jensen, 2013;Mäkelä et al, 2015;Westman et al, 2008). Westman et al (2008) reported that the number of trips did not predict WFC but the level of WFC varied among women during pre-, on-and after-trip stages to an extent that was statistically significant.…”
Section: International Business Travel and Wfcmentioning
confidence: 99%
See 2 more Smart Citations
“…There are at least three earlier studies focussing on work-family or work-life interaction among IBTs ( Jensen, 2013;Mäkelä et al, 2015;Westman et al, 2008). Westman et al (2008) reported that the number of trips did not predict WFC but the level of WFC varied among women during pre-, on-and after-trip stages to an extent that was statistically significant.…”
Section: International Business Travel and Wfcmentioning
confidence: 99%
“…However, the small number of respondents (n ¼ 66, 70 percent males) and the limited intensity of the participants' traveling (4.2 trips/year) may have affected the results of that particular study. The second cross-sectional study by Mäkelä et al (2015) showed that the duration of business trips, that is, number of traveling days during the past 12 months, in particular, was related to high work-to-life conflict (i.e. conflict in the personal life in general, including aspects other than family-related ones).…”
Section: International Business Travel and Wfcmentioning
confidence: 99%
See 1 more Smart Citation
“…It may stimulate achieving a better work-life balance. Such positive enrichment experiences are often forgotten in the literature, where there tends to be a focus on the conflict perspective (Mäkelä et al 2015;Mäkelä and Suutari 2011). Moreover, family members can also be a source of social support and thus provide important backing for the international employee.…”
mentioning
confidence: 94%
“…Similarly, the major negative characteristics of short-term assignments typically include work-life balance issues (Collings et al 2007;Suutari et al 2013). Research on international business travellers has not so far been very intensive, but nevertheless, the findings from such studies have indicated that frequent international travelling causes health and work-life balance issues among others (DeFrank et al 2000;Mäkelä et al 2012Mäkelä et al , 2014Mäkelä et al , 2015Westman and Etzion 2002). The dynamics in balancing work and family lives in the context of international work are being further affected by global trends such as the increase in the numbers of dual-career couples and the increasing number of women in roles involving international responsibilities (McNulty 2014).…”
mentioning
confidence: 97%